Psychological interventions for coronary heart disease - Paul Bennett (Cochrane Database of Systematic Reviews, 2017)
A meta-analysis was conducted on 35 trials involving 10,703 individuals who had experienced a myocardial infarction and were randomised to an intervention involving some form of psychological therapy. Ten of these studies involved individuals with confirmed psychiatric diagnoses. Moderate quality evidence found no reduction of risk for total mortality or revascularisation procedures in comparison to usual care. Low quality evidence found no risk reduction for non-fatal MI although there was a 21% reduction in cardiac mortality. There was also some evidence of benefit on measures of psychological morbidity including anxiety, depression, and stress. It is concluded that psychological interventions may reduce cardiac mortality, although stronger evidence is required before this can be definitively concluded. It is also not clear who benefits most from psychological interventions.